Tax Havens and the Offshore Economy: Implications for Financial Stability and Regulation - Schmidt, Michaela (Momentum Quarterly, 2012)
Tax havens and offshore financial centres open the door for tax evasion, tax avoidance and capital flight. Besides they are one of the major causes of the financial crisis 2007/2008 and keep on endangering the financial market stability. Tax havens and offshore financial centres laid the ground for the occurrence of unregulated financial institutions, the so called shadow banks. Offshore financial centres make it possible for financial institutions to circumvent domestic supervision and regulation. They also boost the competition on taxes and regulations. Every step which is taken to re-regulate tax havens and offshore financial centres is a step to prevent the next financial crisis and to protect employees from the massive costs of financial crisis.